When Someone You Know Has Depression : Words to Say and Things to Do - Noonan, Susan J., 1953- (Book collections on Project MUSE., 2016)
"Following on the success of Managing Your Depression, Susan Noonan's new book is for family members and friends of people with depression or bipolar disorder. A certified peer specialist at McLean Hospital (a comprehensive psychiatric hospital affiliated with Harvard University), Susan draws on her experiences providing support and education for those living with or caring for a person who has a mood disorder. A family member who has a mood disorder affects the entire family. Further, family members and close friends are often the first to recognize the subtle changes and symptoms of depression--and they are also the people who provide daily support to their loved ones, often at great personal price. Caring for someone with a mood disorder differs from caring for someone with a physical medical disorder, in ways that complicate the caregiving role. A concise and practical guide to the daily management of depression and bipolar depression written for the caregiver, the book explains how to reinforce lessons the patient has been taught in therapy, how to role model resilience skills, and how caregivers can and must care for themselves. It describes effective communication strategies and advises how to find appropriate professional help. Its many tables and worksheets convey much needed information in an accessible way. References, Resources, and a Glossary complete the package. Overall the book helps readers navigate the depression or biopolar disorder of someone close to them, providing readers with words to say and things to do as they try to help someone change the course of a sometimes confounding and often disabling illness"--